Penerapan Kombinasi Metode AHP dan ARAS Untuk Menentukan Perusahaan Pengembang Perumahan Terbaik - Prayogo, M. Ari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Housing is a collection of houses built in a certain area and is often identical to where an individual or family lives. The problem in this research is that in selecting a housing development company there are still things that are not quite right. Choosing the wrong housing developer can result in the purchase of a house that does not meet expectations. Therefore, choosing a housing development company is an important decision when buying a house. The aim of this research is to apply a combination of AHP and ARAS methods to determine which housing development company is the best in choosing a housing development company. There are several important things to pay attention to when choosing a housing developer. Therefore, in this research there are criteria parameters used in determining the best housing development company. The criteria used consist of price, quality, processing time, service and satisfaction. These five criteria are used as the basis for assessment in choosing the best housing development company. The results of applying the combination of the AHP and ARAS methods show that of the 5 alternatives there is a company with the largest Ki value of 0.780, namely PT. Ria Bakti as the best housing development company. From the results obtained, this research can provide a solution to the problem of choosing the best housing development company, so that in the future you can avoid regrets when buying housing.